2020
DOI: 10.35891/agx.v11i1.1843
|View full text |Cite
|
Sign up to set email alerts
|

Socio cultural and agricultural local wisdom by cetho indigenous community to preserve the nature

Abstract: The green revolution has left a trail of civilization that is so awesome. Indonesia reached self-sufficiency in food through changes about ways of farming in the community. However, the development strategy which is the big push is gradually getting eliminates the values of local wisdom in farming activity. Farmers are directed in uniformity, from the use of the seeds, fertilizers, and pesticides. As a result, many local plant seed began to become extinct and replaced by new varieties that are sometimes incomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…So local wisdom in an area is an alternative solution to the problems faced in the region itself. In effect, previous people, ancestors, or ancestors have read natural phenomena, understand local natural conditions, and can meet needs by adjusting local natural conditions, and can solve problems with local wisdom [12].Similar to the Kaili da'a tribe who live in Dombu Village, they have unique local wisdom and are suitable to be applied in the local area (local) to control damage to agricultural land. The life of the Kaili da'a tribe is still closely related to local wisdom, especially in terms of agricultural land management that still maintains customary laws, belief in gods and ancestral spirits so that they can control agricultural activities to be environmentally friendly.…”
Section: Resultsmentioning
confidence: 99%
“…So local wisdom in an area is an alternative solution to the problems faced in the region itself. In effect, previous people, ancestors, or ancestors have read natural phenomena, understand local natural conditions, and can meet needs by adjusting local natural conditions, and can solve problems with local wisdom [12].Similar to the Kaili da'a tribe who live in Dombu Village, they have unique local wisdom and are suitable to be applied in the local area (local) to control damage to agricultural land. The life of the Kaili da'a tribe is still closely related to local wisdom, especially in terms of agricultural land management that still maintains customary laws, belief in gods and ancestral spirits so that they can control agricultural activities to be environmentally friendly.…”
Section: Resultsmentioning
confidence: 99%
“…The bee cultivation for the Pakistan farmer is part of their local wisdom to preserve the pollination process in accordance with the ecosystem chain. The indigenous adaptation strategy for African farmer has led them surviving in a drastic climate change [33]. In the Indonesian regions with their variety of cultures, norms, and habits are rich with the local wisdom in farming practice, and it is proved by several researches.…”
Section: The Previous Research Of Farmer Local Wisdommentioning
confidence: 99%
“…(Hong & Sun, 2020) said that local wisdom in some places have relation with religion, or derived from religion or belief. (Prayoga, Riezky, Syuhada, & Prayoga, 2020) showed that local wisdom commonly had been obtained from previous generations and being practice daily. How those local wisdom had born still become a secret, but people believe that what their ancestors were doing are correct and need to be preserved.…”
Section: Local Wisdommentioning
confidence: 99%
“…Local wisdom is not only related to solidarity among the people but has been rooted in the community activities in farming and its efforts to achieve ecological balance (Levis, Sukesi, Sugiyanto, & Yuliati, 2017;Prayoga et al, 2020).…”
Section: Farmers' Local Wisdom On Natural Resourcesmentioning
confidence: 99%